(untitled) (Studia Prawnicze / The Legal Studies, 1983)
Marriage settlement is a legal transaction defining the principles of matrimonial property relations. It should be called an organizational contract. Depending on its type and time of the conclusion it results in the emergence, change or cessation of the legal joint property relation., Such a contract cannot be concluded by a minor without his statutory representative’s consent and permission of the court. Marriage settlement can be concluded with a term clause. It may be dissolved. Marriage settlement is binding ex lege, therefore in case of the revocation of the declaration of legal incapacity of the spouse, it is not necessary to conclude it.